Effect of Physicochemical Properties of Co and Mo Modified Natural Sourced Hierarchical ZSM-5 Zeolite Catalysts on Vanillin and Phenol Production from Diphenyl Ether - Anita Nur Ramadhani; Iman Abdullah; Yuni Krisyuningsih Krisnandi (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
The conversion of lignocellulose biomass to value-added chemicals is challenging. In this paper, the conversion process of diphenyl ether (DPE) as a model lignin compound to phenol and vanillin compounds involved a bifunctional catalyst in reaching the simultaneous one-pot reaction in mild conditions with a high yield product. The catalysts used in this conversion are hierarchical ZSM-5 zeolites and their cobalt oxide and molybdenum oxide impregnated derivate. The ZSM-5 zeolites were synthesized using alternative precursors from natural resources, i.e., Indonesian natural zeolite and kaolin. The physicochemical properties of the catalysts were determined with various characterization methods, such as: X-ray Diffraction (XRD), Fourier Transform Infra Red (FT-IR), Scanning Electron Microscope - Energy Dispersive X-ray (SEM-EDX), X-ray Fluorescence (XRF), Surface Area Analyzer (SAA), and NH3-Temperature Programmed Desorption (NH3-TPD). The catalytic activity on conversion of DPE substrates showed that the MoOx/HZSM-5 produced the highest %yield for phenol and vanillin products; 31.96% at 250 °C and 7.63% at 200 °C, respectively. The correlation study between the physicochemical properties and the catalytic activity shows that the dominance of weak acid (>40%) and mesoporosity contribution (pore size of ~ 9 nm) play roles in giving the best catalytic activity at low temperatures. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).